Reimagining professional competence in physical education - Catherine D. Ennis (Motriz: Revista de Educacao Fisica, 2013)
Physical educators have critical roles to play in assisting communities and schools to increase physical activity for all citizens. They can assist classroom teachers in increasing physical activity in the academic school day and can serve as school wellness directors to increase the amount of physical activity students and school staff members receive during the day. Additionally, physical educators can implement innovative approaches to physical education curricula to enhance students' opportunities to be active and to learn concepts to assist them to be physically active now and for a lifetime. When implementing evidence-based approaches to physical education, teachers need to teach the curriculum coherently and with fidelity. New programs such as Science, PE, & Me! and the Science of Healthful Living provide opportunities for students to examine the effects of exercise on their bodies in a physically active, learning-oriented approach to physical education.